In vitro antifungal effect of endophytic fungi of creole cucurbits of Yucatan - Montañez-De Azcué, Diego; Cristóbal-Alejo, Jairo; Uc-Várguez, Alberto; Moo-Koh, Felicia Amalia; Tun Suárez, José María (Ecosistemas y Recursos Agropecuarios, 2024)
Endophytic fungi are plant symbiont microorganisms, diverse and abundant in tropical regions, with great potential as biocontrol agents of agricultural fungal diseases. The objective of the present work was to evaluate in vitro antifunfal activity of endophytic fungi associated with creole cultivars of Cucumis sativus and Lagenaria siceraria from Yucatán. The endophytic strains were isolated and identified from different organs, to be subjected to dual confrontations and antibiotic tests. Twenty species with antifungal effects against Corynespora cassiicola, Colletotrichum truncatum and Fusarium equiseti were identified, obtaining inhibition ranges of 17.72–100%, 16.51–91.55% and 4.64–91.89%, respectively. Aspergillus flavus, Lasiodiplodia pseudotheobromae and Trichoderma longibrachiatum exhibited the highest percentages of inhibition against the three phytopathogens. Likewise, these three species of endophytes demonstrated an antibiotic effect in their extracts, mainly inhibiting the growth of F. equiseti by up to 46.46%. The L. pseudotheobromae strain has characteristics that give it potential as an antifungal agent, so its applications and growth conditions should continue to be explored. This work represents a first effort to understand the diversity of endophytic fungi in native crops in the region.
Keywords: Antibiosis; Cucumis sativus; Dual cultivation; Lagenaria siceraria; Phytopathogenic fungi